Marketing strategies from the islamic perspective: reviewing the relevance of elements of the marketing mix / Nurul Farhana Nasir …[et al.] - Nasir, Nurul Farhana; Mohd Roslin, Rosmimah; Nasir, Muhammad Arif; Firdaus Nasir, Muhammad Nur (Universiti Teknologi MARA, 2020)
This conceptual paper addresses the relevance of the marketing mix elements in the context of the Islamic business framework. Using the product, price, place of distribution, promotion and people as the bases of discussion, this article relates the implications of riba (interest), gharar (excessive uncertainty), and maisir (gambling) in the context of business. Additionally, the issues of halal and haram are given credence in addressing the implementations of the marketing mix elements. With the Al-Quran and Sunnah as sources of reference, this paper addresses the everyday actions of marketers in establishing and executing their marketing strategies.